EVALUASI POTENSI GENETIS PERTUMBUHAN DAN PRODUKSI VARIETAS UNGGUL BARU TANAMAN PADI (Oryza sativa) DI KECAMATAN BANJAR KABUPATEN PANDEGLANG PROVINSI BANTEN - Kartina AM (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACT The research was aimed to know genetic potential of growth and production of four new superior varieties of rice plants grown in the village Kadu Bale in Banjar sub-district pandeglang Regency of Banten Province. Research was conducted in the village Kadu Bale Banjar District Pandeglang in May until September 2010. The research used a randomized block design with new superior varieties as factor, which consisted of 4 levels with six replications. Parameters were observed: 1) The number of tillers (stems), 2) plant height (cm), 3) Age of panicle appear (HSS), 4) Age of harvest (days), 5) production per ha, and 6) The percentage of empty grains per clump (%). 7) The percentage of attacks Bacterial Leaf Light. The result showed that each variety (Ciherang, Inpari 1, Inpari 7, and Inpari 8 ) had potential interaction to abiotic and biotic environment during the period of its life (one season). Inpari 8 showed the best potential interactions of abiotic and biotic environment during the period of its life (one season).Keywords: rice, production potential, new superior varieties